2012
DOI: 10.2319/051511-333.1
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a method for assessment of cervical vertebral maturation

Abstract: Objective: To evaluate the validity and reliability of the cervical vertebral maturation (CVM) method with a longitudinal sample. Materials and Methods: Eighty-six cephalograms from 18 subjects (5 males and 13 females) were selected from the longitudinal database. Total mandibular length was measured on each film; an increased rate served as the gold standard in examination of the validity of the CVM method. Eleven orthodontists, after receiving intensive training in the CVM method, evaluated all films twice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 20 publications
4
43
0
10
Order By: Relevance
“…In Zhao et al, 31 the CVMM was explained to the observers by means of training sessions, and it showed values of W and k coefficients similar to our best performing sample (JU). Hence, to correctly use the CVMM there might be a need for multiple training sessions to understand how to assess the cervical stage and to acquire a consistent method of evaluation.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In Zhao et al, 31 the CVMM was explained to the observers by means of training sessions, and it showed values of W and k coefficients similar to our best performing sample (JU). Hence, to correctly use the CVMM there might be a need for multiple training sessions to understand how to assess the cervical stage and to acquire a consistent method of evaluation.…”
Section: Discussionsupporting
confidence: 61%
“…20 Some authors have succeeded in the investigation of the reproducibility overcoming the previous methodologic weakness but without exploring the influence of clinical experience on the reproducibility of the CVMM. 20,30,31,34 Indeed, there is little information about the impact of judges' clinical experience on the CVMM, even though it should not be underestimated. 20,35 Therefore, the aim of this study was to evaluate the interobserver and intraobserver reproducibility of the CVMM among three judge panels with different levels of orthodontic experience (OE).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…While some studies have noted a disadvantage in exposing a radiograph of the hand-wrist area and advocate the use of cervical vertebrae maturation staging from an existing lateral cephalogram, 10,11 others have questioned the reliability of the latter. 12,13 Our clinic has found that hand-wrist radiographs are easily implemented, simple to evaluate, and a valuable adjunct to our diagnostic workup.…”
Section: Discussionmentioning
confidence: 99%
“…Debido a que existen factores que afectan la precisión y reproducibilidad del método cvm -como son las mediciones subjetivas del clínico, las formas de las vértebras cervicales que tienen marcadas variaciones de un sujeto a otro, y la calidad de la radiografía-, es preferible correlacionarlo con otros indicadores de crecimiento en la evaluación de la maduración del esqueleto antes de tomar decisiones [31].…”
Section: Vertebras Cervicalesunclassified